David Hughes Parry : a jurist in society - Parry, R. Gwynedd (University of Wales Press, 2010)
As Professor of English Law at the University of London, Sir David Hughes Parry QC laid the foundations for the development of the Department of Law at the London School and Economics into a centre of excellence in legal scholarship. This study offers an account of his career as a lawyer, legal scholar, university policy-maker and law reformer.